Correlation between hematological parameters and cardio metabolic risk factors: report of a study among ethnic tribal women of Tripura, India.(Funded Work) - MS. PURNAJITA SEN; MR. SANDIP DAS; DR. DIPAYAN CHOUDHURI (International Journal of Pharma and Bio Sciences, 2017)
To examine the association between various hematological parameters and components of cardio metabolic risk factors among women from an ethnic tribal community of Tripura, India. Participants were 356 (190 pre-menopausal and 166 post-menopausal) women. Cardio metabolic risk of the subject was evaluated according to consensus statement for diagnosis of general obesity, abdominal obesity and metabolic syndrome for Asian Indians. Hematological parameters like red blood cell (RBC) count, white blood cell (WBC) count, Platelet count, count of neutrophil, lymphocytes, hemoglobin (Hb) concentration, hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), red-cell distribution width (RDW-CV) of the subject were evaluated in a hematological analyzer. Hb showed significantly positive correlation with waist circumference (WC)of the subject. Platelet count, neutrophyl count, HCT and MCH showed significantly positive correlation with systolic blood pressure (SBP). While, lymphocyte and RDW-CV showed significantly negative correlation with SBP. Platelet count and Hb concentration showed significantly positive correlation with diastolic blood pressure (DBP). Total WBC, Hb, MCV and MCH showed significantly positive correlation with triglyceride (TG) level. Total WBC showed significantly negative correlation with high density lipoprotein (HDL-C). While, platelet count showed significantly positive correlation with fasting blood sugar (FBS). Our study findings revealed that various hematological parameters are associated with number of cardio metabolic risk factors and can be used as an indicator for the early detection of individuals at risk for future development of cardiovascular disease.